Inactivation of Glutamine Synthetase-Coding Gene glnA Increases Susceptibility to Quinolones Through Increasing Outer Membrane Protein F in Salmonella enterica Serovar Typhi - Ana R. Millanao; Ana R. Millanao; Ana R. Millanao; Aracely Y. Mora; Claudia P. Saavedra; Claudia P. Saavedra; Nicolás A. Villagra; Nicolás A. Villagra; Guido C. Mora; Alejandro A. Hidalgo (Frontiers in Microbiology, 2020)
Ciprofloxacin is the choice treatment for infections caused by Salmonella Typhi, however, reduced susceptibility to ciprofloxacin has been reported for this pathogen. Considering the decreased approbation of new antimicrobials and the crisis of resistance, one strategy to combat this problem is to find new targets that enhances the antimicrobial activity for approved antimicrobials. In search of mutants with increased susceptibility to ciprofloxacin; 3,216 EZ-Tn5 transposon mutants of S. Typhi were screened. S. Typhi zxx::EZ-Tn5 mutants susceptible to ciprofloxacin were confirmed by agar diffusion and MIC assays. The genes carrying EZ-Tn5 transposon insertions were sequenced. Null mutants of interrupted genes, as well as inducible genetic constructs, were produced using site-directed mutagenesis, to corroborate phenotypes. SDS-PAGE and Real-time PCR were used to evaluate the expression of proteins and genes, respectively. Five mutants with increased ciprofloxacin susceptibility were found in the screening. The first confirmed mutant was the glutamine synthetase-coding gene glnA. Analysis of outer membrane proteins revealed increased OmpF, a channel for the influx of ciprofloxacin and nalidixic acid, in the glnA mutant. Expression of ompF increased four times in the glnA null mutant compared to WT strain. To understand the relationship between the expression of glnA and ompF, a strain with the glnA gene under control of the tetracycline-inducible Ptet promoter was created, to modulate glnA expression. Induction of glnA decreased expression of ompF, at the same time that reduced susceptibility to ciprofloxacin. Expression of sRNA MicF, a negative regulator of OmpF was reduced to one-fourth in the glnA mutant, compared to WT strain. In addition, expression of glnL and glnG genes (encoding the two-component system NtrC/B that may positively regulate OmpF) were increased in the glnA mutant. Further studies indicate that deletion of glnG decreases susceptibility to CIP, while deletion of micF gene increases susceptibility CIP. Our findings indicate that glnA inactivation promotes ompF expression, that translates into increased OmpF protein, facilitating the entry of ciprofloxacin, thus increasing susceptibility to ciprofloxacin through 2 possible mechanisms.